Dietary Pattern and Nutritional Status of Nurses in Nepal and Its Implication: A Case Study - Thapa, Sonu; Maharjan, Kabita (Journey for Sustainable Development and Peace Journal, 2026)
Introduction: This paper aims to assess the dietary pattern and nutritional status among nurses in Nepal. The primary responsibility of nurses is to provide patient care in the clinical sector. Nursing is a profession; their duty is as hard as they work. Therefore, they faced both physical and mental challenges in maintaining good health. Their dietary pattern affects their nutritional status, which is linked to their profession. Inadequate nutrition results in weakness, slower reaction times, and diminished work efficiency. Methods: The quantitative data were collected among 114 nurses as respondents in Nepal Cancer Hospital and Research Centre of Lalitpur, Nepal, through a structured questionnaire. The secondary literature was also analyzed. Both descriptive and inferential statistics were used to analyze the data. Findings: Nearly half of the respondents had a higher BMI value, as 24.6% are overweight, 10.5% obese, and 5.3% underweight. Among the 114 participants, 109 reported as 95.6% reported no physiological change. The respondents who were aged 35 years and above had a higher BMI, 58.7% there is a statistically significant difference (p<0.001) between dietary patterns and nutritional status.